Determining Business Strategy of Seismic Survey Vendor Based on Competitive Advantages: Case Study Elnusa Geoscience - Soewargono, Dadang; Mangkusubroto, Kuntoro; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2012)
Elnusa TBK is one of the biggest oil services in Indonesia established 42 years ago and now have three divisions : 1) Geoscience Services, 2) Drilling Services and 3) Oilfield Services. In the increasingly global competitive oil and gas services industry, company must choose to sharpen its business portfolio.  Competition in the oil and gas services business is quite high, including the entry of several foreign players which forced Elnusa to improve its service and business strategy. This Final Project focus on Geoscience Services division which has the biggest revenue in Elnusa TBK.  Currently Elnusa Geoscience cannot compete with competitors because its fixed cost cannot be reduced.  Therefore, Elnusa Geoscience has to find a way the strategy to compete in this situation.This final project will explore business issues and analyze the factors in oil & gas services industry situation.  Finally this final project provide several alternatives strategy recommendation and implementation plan.. Keywords : competitiveness, oil & gas service company, business strategy